Banish Clutter Forever : How the Toothbrush Principle Will Change Your Life - Sheila Chandra (Vermilion, 2010)
A revolutionary system to help even the most disorganized person live in a state of clutter-free bliss, forever Why is it that even the most disorganized person never seems to lose their toothbrush? How can this simple fact solve all clutter problems? The Toothbrush Principle is a simple yet inspired approach to decluttering any home. Whether in a mansion or a one bedroom apartment, this book will teach readers how to organize according to the unconscious blueprint that naturally tidy people have, so that getting and staying organized is easy. Using this system, readers will learn what to throw away with confidence; how to set up a wardrobe to get much more use out of the clothes they already have; how to work from home productively in a clear, designated space; and how to tame their inbox! Step-by-step, room-by-room, those looking to lose their clutter will soon find that they hardly ever lose things, that massive clear-outs become a thing of the past, and that they never spend more than 10 minutes a day tidying up. Here is the key to stop drowning in piles of clutter and start creating space to live out the life of your dreams!